Mitigation of mercury in water using copper sulfide / Au Yoong Yow Loo - Au Yoong, Yow Loo (2014)
In response to the worldwide mercury contamination contributed by both natural and anthropogenic sources, two different domains of aqueous mercury (II), Hg(II) complexation have been carried out using homogeneous complexing agent, Rhodamine B and heterogeneous complexing agent, Covellite (CuS). The studies of Rhodamine B was conducted using UV-Vis spectroscopy (UV-Vis) where it revealed the instability of Rhodamine B-Hg(II)-Iodide complex in acidic media and it has been resolved either by extraction with benzene or stabilization in water using polyvinyalcohol (PVAl). The studies on Rhodamine B-Hg(II)-Iodide complex were further developed as a non-destructive spectrophotometric method for trace Hg(II) detection. The investigations of CuS in heterogeneous aqueous Hg(II) complexation were conducted using two analytical approach: (i) solution phase analysis i.e. atomic absorption spectrometry (AAS) and cold vapor atomic absorption spectrometry (CVAAS); (ii) solid characterization analysis i.e. powder X-ray diffraction (PXRD), field emission scanning electron microscopy (FESEM), high resolution transmission electron microscopy (HRTEM), energy dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS). From solution phase analysis, the trends of Hg(II) uptake observed were found to dependent on the sorption rate of Hg(II) onto CuS at acidic and alkaline pH. The relatively fast sorption rate of Hg(II) onto CuS at acidic pH can be viewed as the formation of both cubic phase mercury sulfide (Metacinnabar, β-HgS) and monoclinic phase mercuric sulfide chloride (m-Hg3S2Cl2) from PXRD analysis. The relatively slow sorption rate of Hg(II) onto CuS at alkaline pH can be viewed by the sole formation of β-HgS from PXRD analysis. The formation of m-Hg3S2Cl2 was associated with the growth of nanosize ranged needle like architecture namely nano-needle crystallite on the edges of the initial CuS hexagonal plates from FESEM-EDX analysis. The formation of β-HgS was also observed at the edges of the CuS hexagonal plates but its formation was only preferred along the {101} and {100} plane of CuS hexagonal plates from HRTEM-EDX analysis. Furthermore, the uptake of Hg(II) onto CuS at different Hg(II) concentration has been modeled using sorption isotherm models. The equilibrium data suggested that the sorption behavior of Hg(II) onto CuS obeys well to the Langmuir isotherm with the maximum sorption capacity of CuS for Hg(II), Qmax reaching 434.78 mg Hg(II) / g of sorbent at 25°C. Apart from the Hg(II) uptake studies, a consecutive decrease of CuS dissolution and decrease on final solution pH were also detected when initial solution pH is raised. These results showed that an in-situ re-adsorption of Cu(II) and OH- onto CuS has taken place at increasing pH in addition to the ion-exchange of Hg(II) onto CuS. The re-adsorption of Cu(II) and OH- can be viewed as the formation of Cu4(SO4)(OH)6 and its hydrate Cu4(SO4)(OH)6(H2O) from PXRD analysis. Whilst, the re-adsorption of Cu(II) and OH- can be also discussed in term of the formation of Cu(OH)2 and CuO from XPS studies. Moreover, the precipitation of Cu4(SO4)(OH)6 and Cu4(SO4)(OH)6(H2O) has actually led to the growth of additional platelet crystallite in which it has been identified from FESEM-EDX analysis.